2006
DOI: 10.1002/lsm.20300
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal tumors and hepatic metastases differ in their optical properties—relevance for dosimetry in laser-induced interstitial thermotherapy

Abstract: Colon carcinoma tissue has a higher optical penetration depth than healthy colon tissue, which speaks in favor of tumor selectivity for interstitial laser application, since large treatment volumes can be obtained in the tumor. The lack of agreement between primary tumors and their concomitant liver metastases indicates a modification of optical behavior through metastasis. Thermal coagulation of tissue leads to changes in the optical properties, which are clearly less pronounced in carcinoma tissue. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
3
17
1
Order By: Relevance
“…The authors of [32,33] have previously shown experimentally that in the region of the absorption bands of water with maxima at 1450 and 1945 nm, g decreases. This inevitably Wavelength/nm -mucosa, present paper -submucosa, present paper -data of [14] -data of [17] -data of [15] -data of [18] -data of [16] -data of [19] leads to an increase in m s ' and the appearance of bands in its spectrum, a decrease in scattering anisotropy factor in the absorption bands being proportional to the intensity of the absorption bands. The authors of [34,35] developed a theory and built a computer model to explain this behaviour of the reduced scattering coefficient spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [32,33] have previously shown experimentally that in the region of the absorption bands of water with maxima at 1450 and 1945 nm, g decreases. This inevitably Wavelength/nm -mucosa, present paper -submucosa, present paper -data of [14] -data of [17] -data of [15] -data of [18] -data of [16] -data of [19] leads to an increase in m s ' and the appearance of bands in its spectrum, a decrease in scattering anisotropy factor in the absorption bands being proportional to the intensity of the absorption bands. The authors of [34,35] developed a theory and built a computer model to explain this behaviour of the reduced scattering coefficient spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, they were studied in papers [14 - 19]. However, the investigation of the optical characteristics was performed only in the visible wavelength range (360 - 685 nm) [14]; in the ranges of 400 - 1100 nm [15], 300 - 700 nm [16], 300 - 800 nm [17]; and only at particular wavelengths (850, 980 and 1060 nm [18], 476.5, 488, 496.5, 514.5, 532 nm [19]). At the same time, the rapid development of laser technology and the consequent emergence of new types of lasers require the determination of the optical characteristics of tissues in a much broader range of wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade many groups have reported differences in the tissue absorption, and scattering coefficients of native and coagulated tissues [27][28][29][30][31][32][33][34]. Several studies reported an increase in fluorescence in coagulated tissue [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial laser coagulation (ILC) is one of the minimally invasive techniques, and has been applied in the treatment of thyroid diseases, hepatic tumors, symptomatic fibroids, polycystic ovary syndrome, BPH, and so on [5][6][7][8][9] . However, this technique still has some shortcomings for BPH, such as relatively prolonged postoperative catheterization, delayed improvement in symptoms, inferior effectiveness and high retreatment rate compared with TURP [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%